Steps in the identification and compliance process of patient data in the emergency room (Research, Society and Development, 2021)
Objectives: To investigate whether the identification data of patients' wristbands of emergency units correspond to what the Patient Identification Protocol recommends, and verify whether the health team performs the steps of the patient identification process at Emergency Room Units. Methods: descriptive, observational, quantitative and cross-sectional study, carried out between July and September 2017. The sample consisted of 240 patients with more than 24 hours in the emergency room of three public university hospitals in the South of Brazil. Data were collected in a form filled at the bedside. In the analysis, the chi-square test was applied for the categorical variables. The level of significance was α = 0.05. Results: The overall data identification wristband compliance was 85.7%. Among the stages of the identification process, the best result occurred in the "Identification conditions" phase (96.2%). The "Adherence to the identification data conference" (48.3%) was the least executed step. Conclusion: The prevalence and compliance of the patient identification data were high, but, in the identification process, the team's data check phase was low.